VALIDITAS PERJANJIAN PENGIKATAN JUAL BELI SEBAGAI DASAR TERUTANGNYA BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN - Naflah Faadiyah; Muhammad Syaifuddin; Agus Trisaka (Universitas Sriwijaya, 2024)
Law Number 1 of 2022 concerning Financial Relations between Central Government and Regional Governments and Government Regulation Number 35 of 2023 concerning General Provisions of Regional Taxes and Regional Levies amend the provisions on the due date of Acquisition fee Rights to Land and Buildings (BPHTB in Indonesia). One of the changes is that in sale and purchase transaction, BPHTB is due at the time Conditional Sale and Purchase Agreement (PPJB in Indonesia) is made and signed. The determination due date of BPHTB at the time of PPJB gives rise potential violation of transfer/acquisition of rights to land and buildings principle, which must go through the process of factual submission and juridical submission by signing the Deed of Sale and Purchase (AJB in Indonesia) before the Land Deed Official (PPAT in Indonesia). This research discusses the validity of PPJB, which serves as the basis for the due date of BPHTB for sale and purchase transactions. This research is a normative legal study with a statutory, conceptual, and theoretical approach. The research is conducted by analyzing primary, secondary, and tertiary legal materials. Based on the research results, it can be concluded that PPJB is only a preliminary conditional agreement and not a valid basis for the transfer/acquisition of rights to land and buildings. Therefore, using PPJB as the basis of due date of BPHTB is not appropriate because BPHTB, according to Article 1 number (37) of Law No. 1 of 2022, is a tax on acquisition of rights to land and buildings. This also constitutes a violation of transfer/acquisition of rights to land and buildings principle, causing injustice to taxpayers who have been charged BPHTB even though they have not legally acquired the transfer of rights to land and buildings.